An Analysis of the Psychosocial Challenges Faced by the University Students During COVID-19 Pandemic, and the Students' Knowledge, Attitudes, and Practices Toward the Disease - YORGUNER, NEŞE; AKVARDAR, YILDIZ (TURKISH NEUROPSYCHIATRY ASSOC-TURK NOROPSIKIYATRI DERNEGI, 2021)
Introduction: The aims of the present study were 1) to identify the major psychosocial challenges faced by students of a university in Istanbul, during the initial period of the COVID-19 outbreak, 2) to assess how these interacted with their level of knowledge, attitudes, and practices toward COVID-19 and the related health measures in place. Methods: As part of an international research, a total of 2583 university students from Istanbul participated in an online survey, which included questions in several domains including their studies and daily life before and after the outbreak, their concerns and worries about the pandemic, their level of knowledge on COVID-19, their views on the policies implemented by the government and their institution, their attitude and practices toward the protective measures. Results: Majority of the students reported to suffer from financial adversities due to the outbreak. The closure of residential facilities and the cancellation of face-to-face lectures resulted in the vast majority of the students moving back to their family home. Their daily routines were largely replaced by individual home activities, and social interactions shifted almost totally to digital platforms. They also reported high levels of anxiety and worries concerning a wide range of the possible detrimental outcomes of COVID-19, which were in close association with their knowledge, attitudes, and practices towards the disease, as well as their adherence to the policy measures and their satisfaction with the policies of the government. Conclusion: These results may help policymakers in better understanding the psychosocial impacts of COVID-19 on the life of university students, and to develop more comprehensive strategies to address their multifaceted struggles, as well as to improve their compliance with the health measures in the future.
Keywords: COVID-19; university students; psychosocial; knowledge; attitude; practice; GENDER-DIFFERENCES; PERCEPTIONS; RESPONSES; STRESSORS; ANXIETY; FEAR